Numerical simulation study on the construction of cut off walls using high-pressure jet grouting based on SPH method - Liu, Da; Ye, Zhi-wei; Xie, Wei-jiang; Gao, Jiang-lin; Hu, Song-tao; Li, Yan; Chen, Fang (Frontiers in Earth Science, 2024)
The optimization of parameters for the construction of cut off walls using high spray method plays a crucial role in improving the permeability stability of hydraulic structures and ensuring the safe operation of water conservancy projects. However, limited by existing research methods, there is currently a lack of systematic research on the influence of construction parameters on the quality of cut off walls. This study fully considers the characteristics of high-speed slurry jet and soil dynamic failure in numerical simulation of the construction of cut off walls using high spray method. Based on the SPH method, a two-dimensional plane strain model of high-pressure jet grouting was established, and the influence of aperture, grouting pressure, and hole spacing on the failure process of soil and the quality of cut off walls is systematically analyzed. The results show that the soil mainly exhibits tensile failure under the continuous action of high-speed cement slurry during the construction of cut off walls using high spray method. Reducing the aperture and grouting pressure, as well as increasing the hole spacing, are not conducive to forming a continuous and dense impermeable wall. Compared to grouting pressure, the influence of aperture and spacing on the quality of cut off walls is more significant. When the aperture is 0.6 m, the grouting pressure is 32 MPa, and the hole spacing is 0.8 m, the quality of cut off walls is great. Finally, the simulation results of this paper were preliminarily verified by combining the construction of cut off walls using high spray method in the flood control project in Luotang Township, Jiangxi Province, China. The findings can provide reference for optimizing the construction parameters of cut off walls using high spray method.